Polímeros auto regenerativos: um estudo envolvendo a química supramolecular e a ciência dos polímeros - Pinola, Livia Guarizo (Universidade Federal de São Carlos, 2025)
Self-healing polymers are materials capable of autonomously repairing damage or responding to external stimuli, such as light, heat, or pressure changes, without the need for direct human intervention. These smart polymers utilize principles from polymer science and supramolecular chemistry to facilitate regeneration by leveraging reversible chemical interactions, including hydrogen bonding, van der Waals forces, and metal-ligand complexation. Self-healing can be classified as intrinsic when it arises from the material’s inherent properties or extrinsic when it relies on healing agents encapsulated in micro- or nanocapsules. The regeneration mechanisms involve physical processes (chain diffusion, shape memory), chemical interactions (supramolecular interactions, reactive chain ends), or hybrid approaches. These materials have broad applications in industries requiring enhanced durability, such as civil engineering, electronics, and biomedical fields, while also promoting sustainability by reducing waste and replacement costs. The development of smart self-healing polymers offers significant advantages, including increased longevity, reduced maintenance costs, and a positive environmental impact, making them promising for various applications in engineering, electronics, and medicine. This review concludes that integrating supramolecular chemistry with polymer science represents a significant advancement in the development of intelligent and sustainable materials capable of meeting growing industrial and environmental demands.
Self healing polymers: a study involving supramolecular chemistry and poluymer science
Keywords: Polimeros; Auto-regenerativos; Supramolecular; CIENCIAS EXATAS E DA TERRA::QUIMICA